Iklan, Citra Merek, Kualitas Pelayanan Terhadap Kepuasan Konsumen dan Keputusan Pembelian - Putu Galih Jananuraga; Ni Putu Nina Eka Lestari (Jurnal Manajemen dan Bisnis, 2020)
ABSTRACTThe purpose of this study was to analyze advertising, brand image, service quality on customer satisfaction and purchasing decisions. Data collection techniques using questionnaires with a sample of 100 respondents. This study uses SEM analysis techniques. The results of this study show, (1) the Ad variable to Consumer Satisfaction is a significant positive effect which has a standardized estimate (regression weight) of 0.298, (2) the Brand Image variable towards Consumer Satisfaction is a significant positive effect that has a standardized estimate (regression weight ) amounting to 0.352, (3) Service Quality variables towards Consumer Satisfaction are significant positive influences which have standardized estimate (regression weight) of 0.224, (4) Advertising variables for Purchasing Decisions are not significant positive influences that have standardized estimate (regression weight) amounting to 0.093, (5) Brand Image variables on Purchasing Decisions is a significant positive effect that has a standardized estimate (regression weight) of 0.434, (6) Service Quality variables on Purchasing Decisions is a non-significant positive effect that has standardized esti mate (regression weight) of 0.112, (7) the Consumer Satisfaction variable on Purchasing Decisions is a significant positive effect which has a standardized estimate (regression weight) of 0.352.